Principles and concepts of occlusion in restorative dentistry - Nafeesa Qureshi; Zahid Imran (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2023)
The importance of occlusion to practicing dentists is immense as it plays a key role in the success or failure of restorative procedures. This article attempts to demystify and present an overview of the complex topic of occlusion and its principles which are important for the success of restorative procedures. The article discusses the principles of occlusion as these apply to restorative dentistry. It provides a guide as to what is required to optimize the occlusion for restorative treatment outcomes, including conformative and reorganized approaches. Occlusion and its effect on the temporomandibular joint are also presented. The topic is clinically relevant as it will help the practitioners to understand the key concepts of occlusion and help improve the outcome of their restorative dental procedures.